Transforming TESOL Practices through Cognitive Psychology: A Collaborative Action Research Study on Working Memory and Growth Mindset - Ha Thanh Le; Anh Tam Thi Doan; Hoa Huong Le (Vietnam Journal of Education)
The current collaborative action research investigates the application of cognitive psychology principles in enhancing language learning in secondary English classrooms. It emphasizes how teachers, with a better understanding of cognitive processes, can implement strategies informed by cognitive psychology to improve student learning outcomes. Focusing on a single teacher and a cohort of secondary school learners in Grade 7 over the course of one semester, the study integrates action research in promoting teacher critical reflection. Cognitive and educational psychology principles are translated into practical strategies related to course planning, syllabi, lead-in activities, feedback, and learning-focused assessments. The findings suggest that teacher understanding about cognitive and educational psychological factors such as attention, working memory and growth mindset can play a critical role in enhancing language learning. For students, these strategies lead to improved engagement, greater agency and test anxiety alleviation. For the teacher, a deeper understanding of cognitive principles provides greater control over the teaching process and facilitates the development of effective teaching strategies. This research underscores the critical and practical role of collaborations between researchers and TESOL practitioners in comprehending cognitive factors to effectively implement learner-centered teaching methods and activities, thereby cultivating a highly responsive and impactful learning environment.